APLIKASI BERBAGAI KONSENTRASI ZAT PENGATUR TUMBUH UNTUK MENINGKATKAN PERTUMBUHAN BIBIT NENAS (Ananas comosus L.) - Pelio, William Jeverson; Pasigai, Muhammad Anshar; Sarro, Dastar (AGROTEKBIS, 2018)
The aim of this research was to determine the effects of growth regulators (ZPT) Growtone on pineapple seed growth (Ananas comosus L). The research used a Randomized Block design with seven treatmentsconsisting of without plant growth regulator, concentration 2 g Growtone/stem cutting,4 g Growtone/stem cutting,6 g Growtone/stem cutting, 8 g Growtone/ stem cutting, 10 g Growtone/stem cutting dan 12 g Growtone/stem cutting.All treatments were replicated 3 times, so there were 21 experimental units. The observation variables included plant height, leaf number, root length, and total fresh weight. Theconcentrations of theplant growth regulator (ZPT) Growtone at 2-12 g/stem cutting resulted in higher plant height, larger number of leaves and roots, longer root and largert fresh weight of the plant than without the growth regulator.